Pengaruh Motivasi, Kepemimpinan Transformasional, dan Kepuasan Kerja Terhadap Kinerja Pegawai BPDASHL Citarum-Ciliwung - Sriyani; Hubeis, Aida Vitayala Sjafri; Ramly, Amir Tengku (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The bureaucracy reform program aims to achieve high employee integrity, create responsible employees and the ability of employees to provide excellent service. The Citarum-Ciliwung Watershed and Forest Management Center (BPDASHL) has the task of serving the community in the field of forest and land rehabilitation along the Citarum-Ciliwung watershed so that its employees are expected to have good performance. This study aims to examine the effect of motivation, transformational leadership and job satisfaction on the performance of BPDASHL Citarum-Ciliwung employees. The data used is primary data in the form of questionnaire results from 45 respondents who are civil servants of BPDASHL Citarum-Ciliwung. The data was processed using Microsoft Excel tools, analyzed descriptively and analyzed using the Structural Equation Modeling method and the Partial Least Square approach. The results showed that motivation had a positive and significant effect on employee performance, job satisfaction had a positive and significant effect on employee performance, while transformational leadership had no positive effect on employee performance. Motivation is influenced by the desire to work well according to performance targets. Employee performance does not depend on the way the leader leads because the employees perform well in accordance with the determination they have in completing the work. Satisfaction is created because the results are in accordance with the target both in terms of quality and quantity and have succeeded in the success of the office's performance. Keywords: employee performance, job satisfaction, motivation, PLS-SEM, transformational leadership